RANCANG BANGUN SISTEM INFORMASI ALOKASI DAN MONITORING PERMINTAAN KENDARAAN OPERASIONAL PERUSAHAAN - Gita Mustika Rahmah; Nisrina Nur Fitrandi; Denny Rianditha Arief Permana (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2022)
PT XYZ is a manufacturing company engaged in the automotive sector and produces vehicle components with the main products being the propeller shaft and rear axle. The vehicle request process is one of the services provided, which functions as the management and monitoring of the company's operational vehicle requests specifically for the benefit of company activities. In managing operational vehicle requests, employees who need vehicles must fill out a request form in the form of a paper file and ask for approval from their superiors, then the General Affairs Department records vehicle requests into Oracle and Microsoft Excel applications. Storage of data in various media causes the search to be time-consuming, besides the data collection process that is carried out repeatedly with the same data will be prone to recording errors or calculation errors. And when there is a change in data that is not immediately changed in all data collection media, there can be a risk of data being out of sync with data in the General Affairs Department. To overcome this problem, we need a computerized information system with centralized and integrated storage media between parts. The information system development method used is Rapid Application Development (RAD). System design using Use Case Diagrams, Activity Diagrams, Sequence Diagrams, and Deployment Diagrams. Meanwhile, for data modeling using Entity Relationship Diagrams (ERD) and data dictionaries, as well as designing navigation systems using Windows Navigation Diagrams (WND) and the programming language used is PHP using Laravel and PostgreSQL frameworks as databases used. The existence of a vehicle request information system can make it easier for the General Affairs Department to receive vehicle request information quickly for use in making decisions and help shorten the vehicle allocation process time.Â Keywords: Information System, Vehicle Request, UML, PHP, PostgreSQL